2017
DOI: 10.22377/ijgp.v11i02.922
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction: The study was conducted to evaluate the drug utilization pattern of Ayurveda, Unani medicines and folk medicine in comparison to the drug from the modern system (allopathy system) in rural areas of Mewat, Haryana. Materials and Methods: The study was cross-sectional questionnaire-based community survey. The 300 healthy adult male volunteers more than 18 years of age participated in the survey in city Nuh of the district Mewat after obtaining the oral consent. All the participants were literate. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Still more awareness about these systems is required to facilitate integrative medicine in healthcare settings. 4 Jaiswal K, Bajait C, Pimpalkhute S, et al (2015) conducted a study -A patient"s perspective on knowledge, attitude and practice of complementary and alternative medicine‖ in Maharashtra, India. This was a cross-sectional, questionnaire based survey including 100 patients attending out-patient department of a tertiary care teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Still more awareness about these systems is required to facilitate integrative medicine in healthcare settings. 4 Jaiswal K, Bajait C, Pimpalkhute S, et al (2015) conducted a study -A patient"s perspective on knowledge, attitude and practice of complementary and alternative medicine‖ in Maharashtra, India. This was a cross-sectional, questionnaire based survey including 100 patients attending out-patient department of a tertiary care teaching hospital.…”
Section: Introductionmentioning
confidence: 99%
“…A comparative study (Imran et al, 2017) conducted to evaluate the utilization of Ayurveda compared the use of modern medication by adults older than 18 (mean age 20+-2.33) of rural North India, and revealed that there was utilization of Ayurveda (62%) and traditional therapies (76%) for various afflictions. Further, it mentioned that 60% of the respondents preferred to take complementary medicine and that 71% considered complementary medicine more effective than conventional treatments, while 83% would like to recommend complementary medicine to their family and friends (Imran et al, 2017).…”
Section: Introductionmentioning
confidence: 99%